Analysis of the Characteristics of Respondents with the Incidence of Hypertension Disease at the One Million Glasses Examination - Wicaksono, Adhimas Setyo; Nur Aditya, Dwi Martha; Setianto, Budhi; Agus Aan Adriansyah (Syntax Literate, 2024)
Degenerative diseases are one of the major health problems in Indonesia, especially among the elderly population. This study aims to describe the prevalence of degenerative diseases detected during the one million spectacles screening programme at Brawijaya Military Command, Surabaya City. Using a descriptive approach, this study identifies the most common types of degenerative diseases found and analyses their influencing factors. The method used in this research is quantitative research with a cross sectional approach conducted at the One Million Glasses Check-up at Kodam Brawijaya, Surabaya City. The population in this study were all elderly participants who were measured 698 respondents. The sampling technique used total sampling where the entire population became the sample of this study, the sample of this study was 698 hypertension participants. Data collection was carried out in June 2024. Data analysis was carried out using the Chi Square test. It was found in this study that there was a relationship between anxiety and smoking habits on the incidence of hypertension while for abdominal circumference, body mass index and age range there was no relationship related to this.